Linear Programming / Methods and Applications - Gass Saul I (Mcgraw Hill Book Company, 1975)
Preface, Introduction, General Discussion, Mathematical Background, Methods: Theoretical and Computational, The General Linear-Programming Problem, The Simplex Computational Procedure, The Revised Simplex Method, The Duality Problems of Linear Programming, Degeneracy Procedures, Parametric Linear Programming and Sensitivity Analysis, Additional Computational Techniques, Applications, The Transportation Problem, General Linear-Programming Applications, Nonlinear Programming, References, Index.